Analysis Of Construction of Architectural Monuments in Shahrisabz - Shadmanova Z.S; Maksudova G.A; Xoltayeva A.K (Zien Journals, 2021)
Shahrisabz is the city of Amir Temur, where everything is connected with his name in one way or another. His father Muhammad Taragay and his spiritual teacher Shamsiddin Kulol are buried here, and the graves of his eldest sons Jahangir Mirza and Umarshaikh Mirza are located here. The great Sahibkiran himself thought that his soul would fly to the throne here. He even prepared the mausoleum. But fate decided otherwise…
Keywords: Shakhrisabz; Oksaroy; Jahongir Mirza mausoleum; historical monument